Thermal inactivation kinetics and effects of drying methods on the phenolic profile and antioxidant activities of chicory (Cichorium intybus L.) leaves - Li, Ran (Sci Rep, 2018)
The thermal inactivation kinetics of enzymes, including polyphenol oxidase (PPO) and peroxidase (POD), in chicory (Cichorium intybus L.) leaves were evaluated. In addition, the influences of different drying techniques (shade drying, hot air drying and freeze drying) on the phenolic profiles and antioxidant activities of chicory leaves were determined. The antioxidant activities of chicory leaves were evaluated on the basis of their 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, reducing power, and 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activity. The results showed that the activation energy for PPO and POD inactivation were 123.00 kJ/mol and 78.99 kJ/mol, respectively. Preliminary treatment with hot water for 3 min at 90 °C was beneficial for preserving the phenolics present in fresh leaves. Hot air drying was better for the phenolics preservation. The hot air-dried and freeze-dried leaves possessed good antioxidant activities. The leaves with higher phenolics contents had better antioxidant activities, which indicated that the preservation of the phenolics was important for maintaining the antioxidant activity of chicory leaves.